2009
DOI: 10.1504/ijmtm.2009.026193
|View full text |Cite
|
Sign up to set email alerts
|

Managing knowledge within the manufacturing enterprise: an overview

Abstract: This paper examines the literature relating to manufacturing knowledge and describes how it contributes to the manufacturing enterprise. The review shows that there is a strong emphasis on design in the manufacturing knowledge research domain, and that detailed design is the main focus for current research. An analysis is carried out according to publication date and consequently trends are identified. The design focus is increasing, and the trends show that the domain is driven by industrial applications. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…In terms of managing and applying knowledge within a manufacturing enterprise, Baxter et al [8] provided an overview of a number of papers related to the topic. The research found that much of manufacturing knowledge is application driven and there is a clear design bias in the literature.…”
Section: Figure 1 Data Information and Knowledge [5]mentioning
confidence: 99%
“…In terms of managing and applying knowledge within a manufacturing enterprise, Baxter et al [8] provided an overview of a number of papers related to the topic. The research found that much of manufacturing knowledge is application driven and there is a clear design bias in the literature.…”
Section: Figure 1 Data Information and Knowledge [5]mentioning
confidence: 99%
“…However, there is a lack of appropriate techniques that can cost effectively capture and represent process ID for assessing and re-assessing the feasibility of realising further performance improvements at the system or enterprise level. This deficiency in current techniques for attaining a better understanding of internal business processes and knowledge intensive operations is also suggested by Bateman and Rich (2003), and Baxter et al (2009). Therefore, the existing techniques cannot be readily applied to the performance context beyond the operations performance ceiling.…”
Section: Related Researchmentioning
confidence: 99%
“…Reviews of manufacturing-related KM [5,6] suggest that the diversity of KM approaches, together with their foci and objectives is comparable to that found in paradigm development. Numerous KM methods are aligned with particular paradigms and other functional aspects of manufacturing organisations, several methods employing ontological approaches to knowledge definition.…”
mentioning
confidence: 90%